Genome-Wide Analyses of Proteome and Acetylome in Zymomonas mobilis Under N2-Fixing Condition - Nisar, Ayesha; Gongye, Xiangxu; Huang, Yuhuan; Khan, Sawar; Chen, Mao; Wu, Bo; He, Mingxiong (Frontiers in Microbiology, 2021)
Zymomonas mobilis a promising candidate for industrial biofuel production is also capable of nitrogen fixation naturally without hindering ethanol production. However, little is known about the regulation of nitrogen fixation in Z. mobilis. We herein conducted high throughput analyses of proteome and protein acetylation in Z. mobilis under N2-fixing conditions and established its first acetylome. The up-regulated proteins mainly belonged to nitrogen fixation, motility, chemotaxis, flagellar assembly, energy production, transportation, and oxidation-reduction process. Whereas, down-regulated proteins were mainly related to energy-consuming and biosynthetic processes. Our protein acetylation analyses revealed 197 uniquely acetylated proteins, belonging to major pathways such as nitrogen fixation, central carbon metabolism, ammonia assimilation pathway, protein biosynthesis, and amino acid metabolism. Further, we observed acetylation in glycolytic enzymes of central carbon metabolism, the nitrogenase complex, the master regulator NifA, and the enzyme in GS/GOGAT cycle. These findings suggest that protein acetylation may play an important role in regulating various aspects of N2-metabolism in Z. mobilis. This study provides new knowledge of specific proteins and their associated cellular processes and pathways that may be regulated by protein acetylation in Z. mobilis. The results of this study will serve as a baseline for future research in the area.